2023
DOI: 10.21037/mhealth-22-24
|View full text |Cite
|
Sign up to set email alerts
|

A pilot intervention of using a mobile health app (ONC Roadmap) to enhance health-related quality of life in family caregivers of pediatric patients with cancer

Abstract: Background The Roadmap mobile health (mHealth) app was developed to provide health-related quality of life (HRQOL) support for family caregivers of patients with cancer. Methods Eligibility included: family caregivers (age ≥18 years) who self-reported as the primary caregiver of their pediatric patient with cancer; patients (age ≥5 years) who were receiving cancer care at the University of Michigan. Feasibility was calculated as the percentage of caregivers who logged i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…These advances led our team to design an mHealth app called Roadmap, which integrates data from non-invasive wearable sensors (Fitbit) and self-reported mood to monitor mental health. Initially developed to provide resilience-enhancing support to patient-caregiver dyads undergoing hematopoietic cell transplantation (HCT), the app was also adapted for other patient-caregiver dyads with cancer ("ONC") [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…These advances led our team to design an mHealth app called Roadmap, which integrates data from non-invasive wearable sensors (Fitbit) and self-reported mood to monitor mental health. Initially developed to provide resilience-enhancing support to patient-caregiver dyads undergoing hematopoietic cell transplantation (HCT), the app was also adapted for other patient-caregiver dyads with cancer ("ONC") [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers from different disciplines are interested in developing evidence-based mHealth interventions for an array of physical and mental health conditions ( 16 ). For example, a previous research study reported that mHealth can be a platform to provide health-related quality of life support for caregivers of pediatric patients with cancer ( 17 ). Progressive Web App (PWA) provides current and scientifically validated information on viral hepatitis and has the capability to reach large audiences and encourage engagement on viral hepatitis prevention ( 18 ).…”
Section: Introductionmentioning
confidence: 99%